(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Aim: In-Vitro research to compare the cyclic fatigue resistance of three rotary NiTi glidepath files in extremely curved simulated root canal. Methodology: Thirty heat treated rotary nickel titanium (NiTi) files were used for analysis in this study. Ten NiTi files were distributed to each group: Group A: ProGlider. Size – 25mm, 15.02, Group B: TruNatomy. Size –25mm, 17.02, Group C: HyFlex GPF. Size –25mm, 15.02. The cyclic fatigue of the NiTi instruments was evaluated using a custom-made experimental setup. NiTi files were tested within simulated 90-degree curvature canal in a metal block until the files were fractured. The shaping block was set-up and consisted of concave tempered steel radius with a specific radius of curvature, i.e 5 mm with a constant degree of curvature of 90o.Number of cycles to failure (NCF) was then measured for each instrument. The one wayANOVA test and post hoc Tukey’s test was performed as statistical analysis to compare the cyclic fatigue of different rotary file. Results: Group C (HyFlex GPF) group has the highest cyclic fatigue value of 13.4 and Group A (ProGlider) had the least value of 5 which was statistically significant with p < 0.01 Conclusions: HyFlex GPFperformed better amongst the other path finding files in simulated extreme canal curvature.